The Dynamic Relationship Among Atrial Pacing, Premature Atrial Beats, Mode Switching, and Atrial High-Rate Episodes in Patients with Sick Sinus Syndrome - Barış Yaylak; Fuat Polat; Cuma Süleymanoğlu (Kardiyovasküler Tıp E Dergisi/E Journal of Cardiovascular Medicine)
Objectives: This study aimed to explore the association between atrial pacing percentage, frequency of premature atrial beats, and mode-switch episodes and the occurrence of atrial high-rate episodes (AHREs) in patients with sick sinus syndrome (SSS) who underwent dual-chamber pacemaker (DDDR) implantation. Materials and Methods: This prospective, single-center, observational study included 60 patients with SSS and Medtronic DDDR pacemakers. Patients with pre-existing atrial fibrillation, ischemic stroke, heart failure, chronic renal failure, or insufficient follow-up data were excluded. Key parameters, such as atrial pacing percentage, premature atrial beats, mode-switch episodes, and AHREs, were evaluated at 1, 3, and 6 months and at 1 and 2 years after implantation. Results: The mean age of the participants was 65.5 years, with 53.3% of them being male. During the first 3 months, atrial pacing percentage showed an inverse correlation with AHREs (83.7±19.8% at 1 month and 85.2±19.9% at 3 months; p=0.026 and p=0.046, respectively). mode-switch episodes and premature atrial beats were significantly associated with AHREs within the first 6 months (mode-switch episodes: 11.2±4.3 at 1 month, 11.4±3.2 at 3 months, and 6.7±3.1 at 6 months; p=0.015, p=0.033, p=0.041; premature atrial beats: 6.8±2.3% at 1 month, 7.1±2.1% at 3 months, and 7.2±1.9% at 6 months; p=0.015, p=0.022, p=0.031). AHRE prevalence increased progressively from 9.7±2.3% at 1 month to 18.1±4.1% at 3 months and 23.3±5.9% at 6 months. However, these associations diminished after 6 months, persisting less significantly at 1 and 2 years. Receiver operating characteristic curve analysis determined a 94.5% atrial pacing percentage cut-off at 1 month, with a sensitivity of 68% and specificity of 82% [area under the curve (AUC): 0.806, p<0.001], and a 94% cut-off at 3 months, with sensitivity and specificity of 68% and 90%, respectively (AUC: 0.801, p<0.001). For mode-switch episodes, a 1.5 cut-off value at both 1 and 3 months yielded sensitivities of 73% and 74% and specificities of 99% and 98%, respectively (AUC: 0.890 and 0.895, p<0.001). Conclusion: This study highlights a time-dependent relationship between pacing parameters and AHREs in patients with SSS. The early post-implantation periods showed significant correlations, which diminished over time. These findings underscore the importance of regular monitoring for optimal management of SSS patients with DDDR pacemakers.